Relationship of Self-Efficacy with Breastfeeding Practices among Primiparous Mothers - Lina Handayani; Fitri Rekyan; Rahmadhani Miftakhul Khusna; Lafi Munira; Jihan Rizka Syafiya La Moma (Jurnal Berkala Kesehatan, 2021)
Provision of breast milk is the most effective way to ensure baby's health and safety. Breast milk has nutritional and non-nutritional benefits both for the health of the child and the mother. WHO recommends exclusive breastfeeding for up to six months, continued for up to two years. Breastfeeding Self-Efficacy is the most powerful factor that can influence the process of breastfeeding and the success of breastfeeding. The purpose of this study was to identify the relationship between self-efficacy and breastfeeding practices among primiparous mothers. The research was a cross-sectional study. The population in this study was mothers who had given birth to a first live baby at the Widuri Primary Clinic. The sample size in this study was 40 primiparous mothers recruited with the total sampling method. Data were collected using the Breastfeeding Self Efficacy (BSES) questionnaire which contains 25 questions about the breastfeeding self-efficacy of the mothers and observation of breastfeeding practices that refer to 16 breastfeeding practice items. Data analysis was used univariate and bivariate analysis. The results showed that there was no relationship between self-efficacy and breastfeeding practice (p-value = 0.215). There is no relationship between self-efficacy and breastfeeding practice.